Silver Binding Nucleolar Organizer Regions Dots in Oral Leukoplakia with Epithelial Dysplasia and Oral Squamous Cell Carcinoma: An In Vivo Study. (30th April 2014) - Mansoor Samadi, Fahad; Thattil Sebastian, Bastain; Singh, Anil; Chandra, Shaleen; Mohammad, Shadab; Singh, Arun; Halappa, Thippeswamy; Samadi, Firoza
Abstract : Silver binding nucleolar organizer regions (AgNOR) in normal oral mucosa (NOM), oral leukoplakia with epithelial dysplasia (ED), and oral squamous cell carcinoma (OSCC) were studied. The mean AgNOR count per nucleus increased from NOM to ED to OSCC. Tissue showing ED in oral leukoplakia and OSCC cases showed higher counts, wider scatter, and smaller size of AgNOR dots in the nuclei. The study seems to suggest that time method has some potential in distinguishing between NOM and oral leukoplakia with ED and OSCC. Studies of larger numbers are needed to arrive at more substantial conclusions.